1985
DOI: 10.1056/nejm198505233122104
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Intraventricular Hemorrhage by Elimination of Fluctuating Cerebral Blood-Flow Velocity in Preterm Infants with Respiratory Distress Syndrome

Abstract: In a previous study of preterm infants requiring mechanical ventilation for the respiratory distress syndrome, we demonstrated a striking association of fluctuating cerebral blood-flow velocity in the first day of life with the subsequent occurrence of intraventricular hemorrhage. Because this fluctuating pattern could be eliminated by muscle paralysis, we conducted a prospective study of preterm infants receiving mechanical ventilation for the respiratory distress syndrome in which we evaluated the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
130
0
6

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(142 citation statements)
references
References 9 publications
6
130
0
6
Order By: Relevance
“…22,23 Both factors contribute to hypoperfusion and reperfusion injuries in premature babies and augment the rupture of involuting germinal matrix vessels, leading to IVH. 24,25 Fluctuations in the levels of hemoglobin were also associated with severe IVH in our study. Shaver et al showed that a lower first hematocrit level during the first 24 h of life was correlated with a higher incidence of IVH.…”
Section: Discussionsupporting
confidence: 69%
“…22,23 Both factors contribute to hypoperfusion and reperfusion injuries in premature babies and augment the rupture of involuting germinal matrix vessels, leading to IVH. 24,25 Fluctuations in the levels of hemoglobin were also associated with severe IVH in our study. Shaver et al showed that a lower first hematocrit level during the first 24 h of life was correlated with a higher incidence of IVH.…”
Section: Discussionsupporting
confidence: 69%
“…[1][2][3] We recently observed that increasing PaCO 2 in ventilated very low birth weight (VLBW) infants during the first week of life is associated with progressively impaired cerebral autoregulation. 4 Further, hypercapnia in animals has been shown to abolish intact cerebral autoregulation.…”
Section: Introductionmentioning
confidence: 99%
“…9,[12][13][14] Using linear mixed models with random effects, individual changes in MCBFV were related to MBP changes; this finding is consistent with impaired autoregulation of cerebral circulation or a pressure-passive pattern in sick preterm infants as reported by other investigators. 4,6,13 Furthermore, we found that associated changes in MCBFV for each unit change in MBP were greater in infants who demonstrated an increase in PACO 2 . These findings suggest that increases in PACO 2 may aggravate cerebral hemodynamic alterations in those with already impaired cerebral autoregulation.…”
Section: Discussionmentioning
confidence: 57%
“…4,5 Elimination of fluctuation in cerebral blood flow has been associated with a lower incidence of IVH. 6 In an attempt to relate cerebral blood flow changes to surfactant administration, the influence of surfactant on cerebral blood flow velocity (CBFV) was studied by several investigators but with conflicting results. [7][8][9][10][11][12][13][14] Most studies involved a small number of patients and used different preparations of surfactant and different techniques of administration.…”
mentioning
confidence: 99%